Analisis Kinerja Daerah Aliran Sungai Berdasarkan Indikator Penggunaan Lahan dan Debit Air pada DAS Unda - TOBAN, EDOARDO WAHYUDI; SUNARTA, I NYOMAN; TRIGUNASIH, NI MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.5, No.4, Oktober 2016, 2016)
Performance Analysis of Watershed Indicators Based On Land Use and Discharge of Water in DAS Unda Watershed (DAS) is an integral ecosystem elements consist primarily of natural resources, water and vegetation and human resources as users of those resources. Unda watershed allegedly decreased function, such as the decline in forest area, increasing critical lands and known to potentially flood. This research was conducted in order to deternine Unda watershed response to changes of use of land in the years of 2006-2013 and the water discharge conditions. DAS performance indicators used are the Precentage of Vegetation Cover (PVC) and Coefficient of Flow Regime (CFR). Method of research is descriptive comparative view of the two parameters, that is the use of land and water discharge. The results showed the prencentage of vegetation cover in the medium category ranges from 55,07% and deceased by 1,87 in 2013. Indicator coefficient of flow regimes gained 67,66 value before it is published Plan of Integrated Watershed Management (2006-2009) included in the medium category and scores 18,8 after being issued Plan of Integrated Watershed Management (2010-2013) with both categories. CFR suspected impairment is not only influenced by the value of the percentage of vegetation cover, but is also influenced by othe factors, such as climate, soil type, vegetation type, the growth phase, vegetation density, how management and others.
Keywords: Watershed performance; Land use; Hidrology Watershed